Kompetensi Pejabat Pembuat Komitmen, Kualitas Sistem Pengendalian Internal, Konflik Kepentingan dan Fraud Pengadaan Barang atau Jasa - Agusfiandifutra, Erfan; Akram, Akram; Pituringsih, Endar (E-Jurnal Akuntansi; Vol 33 No 5 (2023)DO - 10.24843/EJA.2023.v33.i05.p17, 2023)
The aim of this research is to examine the influence of Commitment Making Officer Competency (PPK), Quality of Internal Control System (SPI) and Conflict of Interest on Goods & Services Procurement Fraud (PBJ) with Performance Accountability as moderator. The research was conducted at 40 regional apparatus organizations of the NTB provincial government with a sample of 107 respondents. Hypothesis testing uses a multiple linear regression model, namely Moderated Regression Analysis (MRA). The test results show that PPK Competence and SPI Quality have a negative effect on PBJ Fraud while Conflict of Interest has no effect on PBJ Fraud. This study found that PPK competence strengthens and SPI quality weakens the effect of Performance Accountability on PBJ Fraud, but Conflict of Interest has no effect on PBJ fraud which is moderated by Performance Accountability. Keywords: Fraud in Procurement of Goods/Services, Commitment Making Officers (PPK), Internal Control System (SPI), Conflicts of Interest, Performance Accountability